PENGARUH SOSIAL MEDIA MARKETING, CONTENT DAN ONLINE REVIEW TERHADAP LOYALITAS PENGUNJUNG KEBUN BINATANG RZOO & PARK - Wani Saragih, Tri; Nurnabilla, Siti; Gunawan, Didik; Mardayanti, Imelda (Berajah Journal, 2025)
This study aims to determine the effect of social media marketing (X1) Contetn (X2 and Online Review (X3) on visitor loyalty (Y) at the Rzoo&park case study follower @rzooandpark. This research was conducted for 2 months starting from February-april 2025. The research method used was the online survey method. The population in this study was all followers @rzooandpark namely 6.631 followers. The sample technique uses accidental sampling, which amounted to 98 obtained from the calculation of the Slovin formula above with a margin of error of 10%. Data collection using a questionnaire by utilizing google form. Based on the results of the determinant coefficient analysis test, it is known that R Square in the Summary model is 0.907. it was concluded that 91% of visitor loyalty can be explained by social media marketing, content and online review, while the remaining 9% is influenced by other variables that are not studied